The Influence Of Brand Image, Product Quality, And Customer Value On Erha Skincare Purchase Decisions In Batam City - Sipahutar, Lamtumiar; Wasiman, Wasiman (Fakultas Bisnis, 2025)
Companies must compete to continue to develop products with new creativity and innovation so that products can be marketed well so that they can achieve success in fierce competition. Different product development efforts may provide an effective and inventive approach for organizations to provide novel product offers, resulting in a decision made by both the company and the buyer. Similarly, Erha's skincare products are competing in the Indonesian beauty business. The goal of this study is to find a favorable correlation between brand image, product quality, and customer value and buying decisions. This study is based on a sample of 100 Batu Aji respondents. This study uses a non-probability sampling technique with purposive sampling. The results of this study are that brand image has a positive and significant effect. The quality of the Product had a positive and significant effect. The customer value had a positive and significant effect. Brand image, product quality, and customer value have a positive effect simultaneously and significantly on purchasing decisions with a significant value. The study's findings are clear: brand image variables, product quality, and customer value significantly influence purchasing decisions for ERHA skincare products in Batam City.The study's findings are clear: brand image variables, product quality, and customer value significantly influence purchasing decisions for ERHA skincare products in Batam City.